Adjusting function of MoS2 on the high-speed emergency braking properties of copper-based brake pad and the analysis of relevant tribo-film of eddy structure. (15th March 2020) - Zhang, Peng; Zhang, Lin; Wei, Dongbin; Wu, Peifang; Cao, Jingwu; Shijia, Cairang; Qu, Xuanhui
Abstract: In this paper, by studying the high-speed emergency braking performance of copper-base brake pads with different MoS2 contents and the corresponding structure of tribo-film, the adjusting function of MoS2 was revealed, which is mainly achieved by the reaction of MoS2 with Cu and Fe. The hard reaction products enhance the strength of the matrix and thus increase the resistance of plastic deformation. However, excessive addition of MoS2 in the matrix leads to the reduced particle size of Fe and the increased matrix discontinuities. Those reduce the deformation resistance of friction surface and the ability to hinder the movement of substances on friction surface, thereby resulting in formation of eddy structure on friction surface of the samples containing high content of MoS2 during high-energy braking. For the sample containing the optimum content of 2 wt % MoS2, the friction coefficient is relatively high and the wear loss is only 17.13% and 5.05% of the samples without MoS2 and with 10 wt % MoS2, respectively. The abnormal high wear loss and the reduction of friction coefficient is mainly determined by the dynamic process of formation and delamination of the eddy structure.